Etnografi Komunikasi Komunitas Dulmuluk Dalam Pelestarian Kesenian Tradisional Sumatera Selatan - arafah, muh mutazim; Muhammad Imam Syah Bangsa (Jurnal Intelek Insan Cendikia, 2024)
Abstract This research focuses on the role of communication in preserving traditional arts in the Dulmuluk community, South Sumatra. Using an ethnographic communication approach, this research explores verbal and non-verbal communication patterns that occur in the community and how this influences efforts to preserve traditional arts. The findings show that communication in its various forms is a key factor in maintaining and developing the cultural heritage of the Dulmuluk community. The recommendations provided include conservation strategies that actively involve the community and use the various types of communication that have been identified.